Datura metel SEED NANO CHITOSAN EXTRACT GEL’S EFFECT ON ANGIOGENESIS WOUND HEALING OF WISTAR RAT - Asriningrum, Vika; Bramanti, Indra; Ardhani, Retno (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Datura metel possesses anti-inflammatory properties useful for treating oral mucosal injuries common in children, where healing relies on angiogenesis. Nano chitosan technology addresses herbal bioavailability issues. This study investigated the effect of 1% Datura metel seed nano chitosan extract gel on angiogenesis in Wistar rats. Methods: Eighteen Wistar rats were divided into three groups: 1% Datura metel seed chitosan extract, 1% nano chitosan extract, and a control group. Gels were applied to mandibular gingival wounds with assessments on days 3 and 5. Histological angiogenesis counts were analyzed using two-way ANOVA (p<0.05). Results: Significant differences in angiogenesis counts were found among the chitosan extract, nano chitosan extract, and positive control groups. Furthermore, variations in angiogenesis counts were observed between day 3 and day 5 across all groups. Conclusion: The 1% Datura metel seed chitosan extract gel demonstrated a greater effect in triggering angiogenesis compared to the 1% nano chitosan extract and the positive control.